EXPLORING THE DYNAMICS OF LEADERSHIP STYLE IN FATONI UNIVERSITY THAILAND - Nizam, Mohammad Firdaus; Parasuraman, Balakrishnan; Hasan, Hazriah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
This study investigates the association of sustainable operations practices (SOPs) to institution’s performance in waqf management in higher education institutions with an emphasis on Fatoni University, Thailand. We systematically reviewed the literature and meta-analysed the correlations to evaluate the direction and strength of the SOP performance relationship and complemented this with qualitative insights from selected case studies. The results show a strong positive relationship, as 14 empirical relationships have found significant positive correlations. It indicates that the adoption of SOPs improves the efficiency, accountability, transparency and long-term sustainability of waqf institutions. There were an additional 12 relationships moderated by leadership style, institution’s culture, governance structure and institution’s environment which indicated that the effectiveness of SOPs depends on the internal and external institutios conditions. These results support the contingency theory that institutions effectiveness depends on the fit between the orientation of leadership and the environmental context. Limitations of the study include a small number of empirical studies that report the statistical details (correlations, effect sizes, standardized coefficients) required for robust meta-analysis. From a practitioner perspective, the study points to the importance of context sensitive leadership, governance and institutions reforms to get the best out of SOPs. This study contributes its multidimensional approach which combines quantitative meta-analysis and qualitative case evidence for a more inclusive understanding of the effect of sustainable operations practices on waqf management performance.